Sierra Leone : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2009)
This Selected Issues paper describes the monetary transmission mechanism in Sierra Leone. The paper uses a vector autoregression model to explore the links between policy changes by The Bank of Sierra Leone and real variables, such as output and prices. The paper describes Sierra Leone's economic environment and institutions, and also looks at the main channels of monetary policy transmission commonly identified in the literature. Empirical evidence is presented, along with findings and policy recommendations. The paper also describes developments in the external sector, and assesses competitiveness using survey-based indicators.